Suppression of tumorigenicity and metastatic potential of melanoma cells by transduction of interferon gene - Lykhova, A.A.; Kudryavets, Yu.I.; Bezdenezhnykh, N.A.; Semesiuk, N.I.; Adamenko, I.N.; Vorontsova, A.L. (Вiopolymers and Cell, 2014)
The aim of this study was to investigate an inhibitory effect of baculovirus-mediated transduction of the murine interferon-beta gene on mouse melanoma in vitro and in vivo. Methods. Studies were performed on B16 mouse melanoma (MM-4 cell line). Transduction, immunocytochemical and tumor cell biology approaches have been used in this study. Results. Transduction of MM-4 cells by the recombinant baculovirus with IFN-beta gene is accompanied by morphological changes of tumor cells, suppression of cell proliferation, significant inhibition of platting efficiency of cells and their colonies formation in semisolid agar. Moreover, transduction of melanoma MM-4 cells by the baculovirus IFN-transgene leads to inhibition of tumorigenicity and metastatic ability of the cells in vivo. The intravenous administration of recombinant baculovirus vector with IFN gene inhibits growth of metastases induced in the lungs of mice by intravenously injected tumor cells. Conclusions. Transduction of mouse melanoma cells by the recombinant baculovirus with murine IFN-beta gene inhibits their proliferative potential, tumorigenicity and metastatic activity. Мета. Вивчення інгібувального ефекту трансдукції клітин меланоми миші рекомбінантним бакуловірусом з геном інтерферону-бета миші in vitro та in vivo. Методи. Дослідження проведено на моделі меланоми миші B16 (клітинна лінія MM-4) з використаннням трансдукції клітин рекомбінантним бакуловірусом, імуноцитохімічного аналізу та методів дослідження біології пухлинної клітини. Результати. Трансдукція клітин ММ-4 рекомбінантним бакуловірусом з геном ІФН-бета миші призводить до змін морфології пухлинних клітин, пригнічення клітинної проліферації, значного інгібування посадкової ефективності та колонієутворювальної активності у напіврідкому агарі. Крім того, трансдукція клітин меланоми ММ-4 бакуловірусом з геном ІФН-бета пригнічує онкогенність і метастатичний потенціал клітин in vivo. Внутрішньовенне введення рекомбінантного бакуловірусного вектора з геном ІФН-бета інгібує ріст метастазів меланоми в легенях мишей, яким внутрішньовенно введено пухлинні клітини. Висновки. Трансдукція клітин меланоми миші рекомбінантним бакуловірусом з геном ІФНбета миші пригнічує їхній проліферативний потенціал, а також онкогенну і метастатичну активність. Цель. Изучение ингибирующего эффекта трансдукции клеток меланомы мыши рекомбинантным бакуловирусом с геном интерферона-бета мыши in vitro и in vivo. Методы. Исследование проведено на модели меланомы мыши B16 (клеточная линия MM-4) с использованием трансдукции клеток рекомбинантным бакуловирусом, иммуноцитохимического анализа и методов исследования биологии опухолевой клетки. Результаты. Трансдукция клеток ММ-4 рекомбинантным бакуловирусом с геном ИФН-бета мыши приводит к изменениям морфологии опухолевых клеток, подавлению клеточной пролиферации, значительному ингибированию посадочной эффективности и колониеобразующей активности в полужидком агаре. Кроме того, трансдукция клеток меланомы ММ-4 бакуловирусом с геном ИФН-бета подавляет онкогенность и метастатический потенциал клеток in vivo. Внутривенное введение рекомбинантного бакуловирусного вектора с геном ИФНбета ингибирует рост метастазов меланомы в легких мышей, которым внутривенно введены опухолевые клетки. Выводы. Трансдукция клеток меланомы мыши рекомбинантным бакуловирусом с геном ИФН-бета мыши подавляет их пролиферативный потенциал, онкогенность и метастатическую активность.